A multi-omics-based investigation into the flavor formation mechanisms during the fermentation of traditional Chinese shrimp paste. (April 2023) - Li, Ying; Leng, Weijun; Xue, Jiani; Yuan, Li; Liu, Hongying; Gao, Ruichang
Graphical abstract: Highlights: 17 key volatiles contribute greatly to the distinct flavor formation of shrimp paste. Tetragenococcus dominated in the whole fermentation process. Chemical reactions, especially Maillard reactions, play an important role in flavor formation. Secondary metabolites and precursors participated in the flavor formation. The formation mechanism of the unique flavor of shrimp paste was elucidated. Abstract: The fermentation process of traditional shrimp paste is closely associated with the production of flavor substances, but the formation mechanism of key aroma components is still unclear. In this study, a comprehensively flavor profile analysis of traditional fermented shrimp paste was carried out by E-nose and SPME-GC–MS. A total of 17 key volatile aroma components with OAV > 1 contributed greatly to the overall flavor formation of shrimp paste. In addition, high-throughput sequencing (HTS) analysis revealed that Tetragenococcus was the dominant genera in the whole fermentation process. Moreover, metabolomics analysis showed that the oxidation and degradation of lipids, protein, organic acids and amino acids produced a large number of flavor substances and intermediates, which laid the foundation for the Maillard reaction in term of generating the distinct aroma of the traditional shrimp paste. This work will provide theoretical support for the realization of flavor regulation and quality control in traditional fermented foods.